Development of Better Aptamers: Structured Library Approaches, Selection Methods, and Chemical Modifications - Brown, Alex; Brill, Jake; Amini, Ryan; Nurmi, Connor; Li, Yingfu (Angewandte Chemie International Edition, 2024)
Systematic evolution of ligands by exponential enrichment (SELEX) has been used to discover thousands of aptamers since its development in 1990. Aptamers are short single‐stranded oligonucleotides capable of binding to targets with high specificity and selectivity through structural recognition. While aptamers offer advantages over other molecular recognition elements such as their ease of production, smaller size, extended shelf‐life, and lower immunogenicity, they have yet to show significant success in real‐world applications. By analyzing the importance of structured library designs, reviewing different SELEX methodologies, and the effects of chemical modifications, we provide a comprehensive overview on the production of aptamers for applications in drug delivery systems, therapeutics, diagnostics, and molecular imaging. Aptamers are highly structured, single‐stranded oligonucleotides that bind to specific targets with high affinity and selectivity. We provide a comprehensive overview of aptamer development strategies that can help facilitate their translation into real world applications, including discussions on how certain secondary structures can be used as scaffolds to build more potent aptamers for diagnostic and therapeutic applications.